Impacts of oak pollen on allergic asthma in the USA and potential effect of future climate change: a modelling analysis. (April 2017) - Anenberg, Susan; Weinberger, Kate R; Roman, Henry; Neumann, James E; Crimmins, Allison; Fann, Neal; Martinich, Jeremy; Kinney, Patrick L
Abstract: Background: Future climate change is expected to lengthen and intensify pollen seasons in the USA, potentially increasing incidence of allergic asthma. We examined the health consequences of present day oak pollen levels and climate-induced changes in oak pollen on asthma emergency department visits in the USA. Methods: We estimated oak pollen season length for moderate (RCP4.5) and severe climate change scenarios (RCP8.5) from 2010 through to 2090 using five climate models and published relationships between temperature, precipitation, and pollen season length. We calculated asthma emergency department visit counts associated with 1994–2010 average oak pollen concentrations and with simulated future oak pollen season length changes using the Environmental Benefits Mapping and Analysis Program (BenMAP-CE), driven by epidemiologically derived concentration-response relationships. Findings: Oak pollen was associated with an estimated 7400, 8800, and 5000 asthma emergency department visits in the northeast, southeast, and midwest USA, respectively, in 2010, with substantial economic damages. Most of these visits (14 600) occurred among children age younger than 18 years. Severe climate change could increase oak pollen season length and associated asthma emergency departments visits in all regions examined in 2030, 2050, 2070, and 2090, resulting in millions of dollars in health-care costs in these US regions through to 2090. Moderate versus severe climate change could mitigate much of the additional burden of oak pollen-related asthma emergency department visits. Interpretation: Although these results were restricted to one pollen type and one health outcome, these results suggest that aeroallergens pose a substantial US public health burden, that climate change could increase US allergic disease incidence, and that mitigating climate change might have benefits from avoided pollen-related health effects. However, wide confidence intervals and several key methodological limitations constrain the strength of these conclusions. As more studies quantify the effects of climate on pollen and pollen on health, this methodology can be applied to additional pollen types and health outcomes. Funding: US Environmental Protection Agency.